Relaxing effects of clenbuterol, ritodrine, salbutamol and fenoterol on the contractions of horse isolated bronchi induced by different stimuli. (February 2020) - Pozzoli, Cristina; Bertini, Simone; Poli, Enzo; Placenza, Giuseppe; Menozzi, Alessandro
Abstract: β2 -adrenoceptor agonists are considered the most effective drugs to counteract bronchoconstriction in horses with asthma, but only clenbuterol is commonly employed in clinical practice. We evaluated the effects of different selective β2 agonists: clenbuterol, ritodrine, salbutamol, and fenoterol on the contractions of isolated bronchial muscle of horses induced by electrical field stimulation (EFS), carbachol, histamine, and KCl. All β2 agonists reduced the amplitude of contraction induced by the different stimuli but with variable efficacy and potency. Fenoterol and salbutamol were more effective than clenbuterol in relaxing the bronchial contractions induced by EFS and histamine, and were able to completely abolish carbachol-induced contractions, unlike clenbuterol and ritodrine. The respective potency values (pEC50 ) of clenbuterol, ritodrine, salbutamol, and fenoterol were 7.74 ± 0.20, 7.77 ± 0.17, 7.30 ± 0.23, 8.01 ± 0.13, for EFS-induced contractions; 8.39 ± 0.26, 5.49 ± 0.28, 6.63 ± 0.14, 7.68 ± 0.11, for carbachol-induced contraction; 7.39 ± 0.27, 7.04 ± 0.28, 6.45 ± 0.34, 7.34 ± 0.22, for histamine-induced contraction; 7.15 ± 0.06, 6.07 ± 0.20, 6.48 ± 0.14, 6.70 ± 0.18, for KCl-induced contraction. Salbutamol and fenoterol showed a higher efficacy than clenbuterol in relaxing horse bronchial muscle pre-contracted by most stimuli. Clenbuterol displayed a good potency but a rather low efficacy, and this may be due to its partial agonist nature; ritodrine showed lower or not significantly different efficacy and potency compared to the other agonists. An evaluation of the clinical efficacy by fenoterol and salbutamol in horses with asthma could be of great interest to assess if they could represent more effective bronchodilators compared to clenbuterol. Highlights: Clenbuterol, ritodrine, salbutamol, and fenoterol relaxed isolated horse bronchi. Salbutamol and fenoterol more effective than clenbuterol on EFS-induced contractions. Salbutamol and fenoterol abolished carbachol-induced contraction completely. Salbutamol and fenoterol more effective than clenbuterol on histamine-evoked contraction. Clinical efficacy of salbutamol and fenoterol in asthmatic horses needs evaluation.